Improvements in the cultivation of plant tissues (Revista Española de Fisiología, 1960)
The aseptic conservation of Plant Tissue Cultures perfor- med in Erlenmeyer flasks stoppered with cotton in humid en- vironments was lost by the development of Filamentous Fungi through the stopper.Sorbic acid, as fungistaticagent, impregnating the cot ton prevenís the microbial spread ;but the humid cotton reduces the access of air.Glass-wool, laterally protected with filature of asbestos, enable to fíame, to avoid the effeets of external spores, and allowing a good aeration constitutes a practical stopper.